Concept and Position of Peremptory Norms (Jus Cogens) in International Law: A Preliminary Study - Handayani, Irawati (Hasanuddin Law Review, 2019)
Peremptory norms or jus cogens hold a unique position in international law. Unlike customary international law and treaty law, they abide no derivation and bind all states regardless of their willingness to be bound. Some scholars had elaborated fundamental theories to answer the theoretical background of jus cogens. However, they have never reached a satisfactory result. This study aims to elaborate the theoretical background of jus cogens and to observe the relationship between jus cogens, obligation erga omnes, and customary international law. The positivists recognize that jus cogens is an imperative norm within state practice and opinio juris. The positivist theory is not in line with the concept that jus cogens bound to states without their consent since every state has their sovereignty and cannot be bound by any kind of provision without consent. The proponents of the natural law theory stated that peremptory norms are inherited from the tradition of natural law so that it is the highest norm in international law that directly binds countries. On the other hand, the public order theory states that international law recognizes important (imperative) norms, which are hierarchically higher than ordinary norms and customary international law to advance the interests of the international community and to preserve the main values of international law. The three theories are considered insufficient to answer the philosophical basis of jus cogens. In its development, therefore, some new theories have been developed to challenge the basis of jus cogens.